Recovery kinetics following sprint training: resisted versus unresisted sprints - Christina A. Liakou; Ioannis G. Fatouros; Athanasios Poulios; Themistoklis Tsatalas; Evangeli Karampina; Panagiota Karanika; Despoina Kaloudi; Anastasia Rosvoglou; Panagiotis Tsimeas; Anna Kamperi; Niki Syrou; Athanasios Gatsas; et al. (European Journal of Applied Physiology, 2024)
Purpose To determine the recovery kinetics of performance and exercise-induced muscle damage following different sprint-training protocols. Methods In a crossover design, ten male and female athletes (20.6 ± 2.4 years) performed 2 × (3 × 20 m: 2 min rest) and 1× (3 × 30 m: 3 min rest) of: (a) unresisted sprints (UST), (b) resisted sprints with 10% of body mass (BM) load (RST10), (c) resisted sprints with 20% BM load (RST20), against a control trial (no-training). Results Blood lactate (mmol/L) increased post-training versus pre-training in all sprint-training trials (6.7 ± 2.4 vs 1.2 ± 0.2, 5.6 ± 2.4 vs 1.3 ± 0.3, 7.3 ± 2.7 vs 1.2 ± 0.3, in UST, RST10, RST20, respectively), as did creatine kinase (U/L) 24 h, 48 h and 72 h post-training (UST: 251 ± 173, 238 ± 154, 209 ± 115 vs 155 ± 9, RST10: 252 ± 134, 240 ± 83, 218 ± 103 vs 164 ± 106; RST20: 237 ± 133, 323 ± 303, 262 ± 184 vs 179 ± 106, respectively). DOMS of knee-extensors (KE) and knee-flexors (KF) increased post-training up to 72 h in all sprint-training trials versus pre-training (ranging from 1.6 ± 1.3 to 3.8 ± 2.8 vs 1.0 ± 0, respectively). Eccentric torque (N m) of the KE of the non-dominant limb, decreased 24 h post-training versus pre-training in all sprint-training trials (UST: 249 ± 49 vs 266 ± 54; RST10: 229 ± 52 vs 273 ± 72; RST20: 253 ± 6 vs 262 ± 56), as did that of the KF of the dominant limb (UST: 135 ± 29 vs 144 ± 26; RST10: 130 ± 29 vs 140 ± 25; RST20: 139 ± 33 vs 142 ± 26). 10-m sprint-time (s) increased 48 h post-training versus pre-training (1.81 ± 0.15 vs 1.77 ± 0.11), and 30-m sprint-time increased 24 h, 48 h, 72 h post-training versus pre-training (4.35 ± 0.36, 4.40 ± 0.44, 4.33 ± 0.41 vs 4.21 ± 0.34, respectively), only in RST20. Conclusions Unresisted and resisted sprint-training induces prolonged reduction of muscle strength (24 h), and sprinting performance (72 h), associated with prolonged increase of DOMS and CK (72 h).

Muscle damage, inflammatory, immune and performance responses to three football games in 1 week in competitive male players - Magni Mohr; Dimitrios Draganidis; Athanasios Chatzinikolaou; Jose Carlos Barbero-Álvarez; Carlo Castagna; Ioannis Douroudos; Alexandra Avloniti; Alexandra Margeli; Ioannis Papassotiriou; Andreas D. Flouris; Athanasios Z. Jamurtas; Peter Krustrup; et al. (European Journal of Applied Physiology, 2016)

Physiological and performance adaptations of elite Greco-Roman wrestlers during a one-day tournament - Ioannis Barbas; Ioannis G. Fatouros; Ioannis I. Douroudos; Athanasios Chatzinikolaou; Yiannis Michailidis; Dimitrios Draganidis; Athanasios Z. Jamurtas; Michalis G. Nikolaidis; Charalabos Parotsidis; Anastasios A. Theodorou; Ioannis Katrabasas; Konstantinos Margonis; et al. (European Journal of Applied Physiology, 2011)

The effects of muscle damage on walking biomechanics are speed-dependent - Themistoklis Tsatalas; Giannis Giakas; Giannis Spyropoulos; Vassilis Paschalis; Michalis G. Nikolaidis; Dimitrios E. Tsaopoulos; Anastasios A. Theodorou; Athanasios Z. Jamurtas; Yiannis Koutedakis (European Journal of Applied Physiology, 2010)

Increased oxidative stress indices in the blood of child swimmers - Sofia Gougoura; Michalis G. Nikolaidis; Iason A. Kostaropoulos; Athanasios Z. Jamurtas; Georgios Koukoulis; Dimitris Kouretas (European Journal of Applied Physiology, 2007)

Comparison between leg and arm eccentric exercises of the same relative intensity on indices of muscle damage - Athanasios Z. Jamurtas; V. Theocharis; T. Tofas; A. Tsiokanos; C. Yfanti; V. Paschalis; Y. Koutedakis; K. Nosaka (European Journal of Applied Physiology, 2005)

Beta-endorphin infusion alters pancreatic hormone and glucose levels during exercise in rats - Ioannis G. Fatouros; Allan H. Goldfarb; Athanasios Z. Jamurtas; Theodore J. Angelopoulos; Jiaping Gao (European Journal of Applied Physiology, 1997)